Studi Kasus Penerapan Evidence Based Practice Oral Cryotherapy Untuk Mencegah Terjadinya Oral Mukositis pada Pasien Kanker yang Mendapatkan Kemoterapi 5-Flurourasil - Ni Ketut Kardiyudiani (Jurnal Keperawatan Notokusumo, 2015)
Background: Chemotherapy is one of the management of cancer by administering a chemical compound (drug) to reduce, eliminate or inhibit the growth of cancer cells. One of the commonly used chemotherapy drugs are 5-Fluorouracil (5-fu) to the toxic effect is oral mucositis. Resulting in impired function of the mouth in general, lower quality of life, pain, malnutrition, even to the delay chemotherapy or adjustment/reduction of dose, this will lead to increased day care of patients in the hospital. Method: The application using the case study method with the application of the evidence based practice (EBN) Settler model. Result: Oral cryotherapy can reduce the incidence of oral mucositis and well tolerated and there were no adverse effects on the local or systemic treatment of oral cryotherapy. Conclusion: The effectiveness of nursing interventions that have been based on the EBN in helping to overcome the problem of oral mucositis in patients receiving chemotherapy 5-fu.